HYDRAULIC FRACTURING ANALYSIS OF LOW PERMEABILTY, HEAVY OIL RESERVOIR TELISA FORMATION, BENTAYAN FIELD - Amril Anshary (Journal of Petroleum and Geothermal Technology, 2022)
There is no proven economic oil production yet from Bentayan’s part of Telisa Layer. However, open hole log from some wells in Bentayan field indicates hydrocarbon presence in TELISA in Bentayan field. GGR study also indicated low value in permeability of Telisa in Bentayan field. Production test in BN-62 indicates oil presence from Telisa with very low influx. To prove the hydrocarbon prospect of Telisa in Bentayan field, operator planned to develop Telisa in BN-62 and BN-21 by conducting hydraulic fracturing using approximately 80,000 lbs of proppant.Early screen out happened when fracturing both wells. After the job, these two wells could not prove economical hydrocarbon production from Telisa. Both wells only have AOFP of 3 BFPD with lack of hydrocarbon indication.Evaluation indicated that the cause this failure on the fracturing job may be caused by smaller value of flow efficiency than it was predicted due to the large permeability zones and formation of multiple fractures that caused pad volume and the slurry pumping flow rate to be less to create the expected fracture geometry. Based on rock property map, BN-95 is suggested to be a candidate to prove the prospect of economical hydrocarbon content in from Telisa. Keywords: well stimulation, hydraulic fracturing, low permeability reservoir, Telisa